Implementasi Budidaya Ikan Nila Merah Berbasis Aquaponik Sebagai Upaya Peningkatan Ketahanan Pangan Dan Edukasi Gizi Bagi Anggota PKK Di Desa Tegal Suruh Kecamatan Sragi Kabupaten Pekalongan - M. Bahrus Syakirin; Tri Yusufi Mardiana; Linayati Linayati; Abdul Halim; Nok Rina Nur Risqi; Desi Diani Putri; Khairunnisa Rizki Purnomo; M Saaid Tsaqif Mughits; Benny Diah Madusari; Hana Nurfitria Rahmah (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Family food security is an important factor in supporting the quality of life of communities. The utilization of fish culture through an aquaponic system can serve as an alternative for the sustainable production of both animal- and plant-based food sources. This community service program aimed to enhance the knowledge and skills of PKK women in Tegal Suruh Village, Sragi District, Pekalongan Regency, regarding the implementation of a nutrition garden based on aquaponics. The methods employed included socialization, training, and hands-on practice in constructing an aquaponic system. The system integrated the culture of 500 red tilapia (stocked in a 6 × 7 m pond with eight hydroponic PVC pipes, each containing seven planting holes, resulting in a total of 56 planting holes cultivated with water spinach (Ipomoea aquatica). The program involved 25 PKK women from Tegal Suruh Village and was conducted in collaboration with the village government and the Pekalongan Regency Fisheries Service, which provided the fish seed. The results demonstrated an improvement in participants’ understanding of aquaponic concepts, red tilapia culture techniques, and water spinach cultivation. Participants showed high enthusiasm and expressed interest in implementing similar systems at the household level. This program has the potential to strengthen household food security, increase community awareness of nutrition, and serve as a means of community empowerment based on local resources.